2019
DOI: 10.3390/plants8120605
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Functions of Gasotransmitters in Plant Responses to Abiotic Stresses

Abstract: Abiotic stress is one of the major threats affecting plant growth and production. The harm of abiotic stresses includes the disruption of cellular redox homeostasis, reactive oxygen species (ROS) production, and oxidative stress in the plant. Plants have different mechanisms to fight stress, and these mechanisms are responsible for maintaining the required homeostasis in plants. Recently, the study of gasotransmitters in plants has attracted much attention, especially for abiotic stress. In the present review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 121 publications
0
15
0
3
Order By: Relevance
“…In addition to NO, two more gaseous signaling molecules (gasotransmitters), hydrogen sulfide (H 2 S), and carbon monoxide (CO) produced within plant cells are an integral part of ABA-dependent stomatal closure as well as other stress conditions. These three gasotransmitters interacted with ABA-signaling during drought ( García-Mata and Lamattina, 2013 ; Yao et al, 2019 ; Gahir et al, 2020 ). Under abiotic stress, ABA could elevate the levels of NO as well as CO or H 2 S. For e.g., ABA activated heme oxygenase (HO), thereby increased CO levels and caused stomatal closure ( Cao et al, 2007 ; Wang and Liao, 2016 ).…”
Section: Aba-interaction With Gasotransmittersmentioning
confidence: 99%
“…In addition to NO, two more gaseous signaling molecules (gasotransmitters), hydrogen sulfide (H 2 S), and carbon monoxide (CO) produced within plant cells are an integral part of ABA-dependent stomatal closure as well as other stress conditions. These three gasotransmitters interacted with ABA-signaling during drought ( García-Mata and Lamattina, 2013 ; Yao et al, 2019 ; Gahir et al, 2020 ). Under abiotic stress, ABA could elevate the levels of NO as well as CO or H 2 S. For e.g., ABA activated heme oxygenase (HO), thereby increased CO levels and caused stomatal closure ( Cao et al, 2007 ; Wang and Liao, 2016 ).…”
Section: Aba-interaction With Gasotransmittersmentioning
confidence: 99%
“…Pro is a kind of organic osmolyte with a wide distribution in plant cells. Previous studies have demonstrated the increase of Pro after the application of signal transmitter agents in defense of abiotic stresses [ 89 , 103 , 104 ]. Pretreatment with exogenous H 2 S increased endogenous Pro content, and the activities and transcription levels of proline-5-carboxylate reductase (P5CR) and proline dehydrogenase (PDH) in foxtail millet, whereas H 2 S scavenger or inhibitor reduced the above effects [ 105 ].…”
Section: Crosstalk Between H 2 S and Other Signal Molecules In Response To Abiotic Stressesmentioning
confidence: 99%
“…Since the past two decades, the role of gasotransmitters in modulating stomatal closure, as a part of plant innate immunity response to protect against biotic/abiotic stress conditions has drawn considerable attention (García-Mata and Lamattina 2013, Scuffi et al 2016, Yao et al 2019. Examples of such gasotransmitters that induce stomatal closure are NO, carbon monoxide (CO) and hydrogen sulfide (H2S).…”
Section: Introductionmentioning
confidence: 99%